Diabetes Mellitus and Infertility: Different Pathophysiological Effects in Type 1 and Type 2 on Sperm Function - Condorelli, Rosita A.; La Vignera, Sandro; Mongioì, Laura M.; Alamo, Angela; Calogero, Aldo E. (Frontiers in Endocrinology, 2018)
Although the prevalence of sub-infertility in diabetic patients in childbearing age is known, the mechanisms by which diabetes mellitus (DM) causes male infertility are not completely explained. This detrimental effect is achieved with a variety of mechanisms that include pre-testicular, testicular and post-testicular pathogenetic moments and can be different in type 1 (DM1) and type 2 (DM2) DM patients because of type of diabetes, duration of disease and glycemic metabolic compensation. Aim of the study was to evaluate whether diabetic disease can be considered a risk factor for infertility considering the etiopathogenetic differences between type 1 (DM1) and 2 (DM2) diabetes mellitus on sperm function. We enrolled 38 DM1 patients and 55 DM2 patients with idiopathic infertility history >12 months, and 100 healthy fertile subjects. The following outcomes were evaluated in optical microscopy and flow cytometry: sperm function (by conventional and biofunctional sperm parameters), signs of urogenital infection/inflammation (by sperm leukocyte concentrations and indices of oxidative stress). Moreover, an andrological evaluation (by didymo-epididymal ultrasound evaluation, serum total testosterone, LH and FSH measurements) was performed in DM1 and DM2 patients compared to controls. Diabetic patients showed a higher risk of becoming infertile and the pathophysiological mechanisms of damage were different in DM1 and DM2. Conventional sperm parameters of diabetic patients are worse than controls (p<0.05). The DM2 caused an inflammatory condition with increased oxidative stress resulting in decreased sperm vitality and increased sperm DNA fragmentation. DM1 altered epididymal voiding causing low ejaculate volume and mitochondrial damage resulting in decreased sperm motility. These findings and evidences support the contention that DM could be regarded as cause of male infertility suggesting that the prevention of diabetic disease in DM2 and the follow-up of seminal parameters in DM1 could prevent fertility decline in these categories of patients.